2018
DOI: 10.1111/ssqu.12481
|View full text |Cite
|
Sign up to set email alerts
|

More on Plagiarism in the Social Sciences*

Abstract: This research presents the results of a follow‐up survey to journal editors more than a decade after Enders and Hoover (Journal of Economic Literature 42(3):487–93). The original survey asked editors about their definition of plagiarism and known cases. This work investigates what, if anything, has changed in regards to how journal editors react to suspected plagiarism and if the definition of plagiarism has changed. In addition to surveying editors of economics journals, we have surveyed many more editors, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…After distributing our questionnaire to these journals and sending out two reminders, we eventually obtained a total of 361 useful responses. The final response rate of 6.12% is low, but comparable to, or even higher than response rates of similar online surveys among journal editors or authors regarding issues related to academic integrity (Hopp and Hoover 2017;Stitzel et al 2018). Nevertheless, our sample covers a wide range of research fields and reflects the distribution of journals over fields.…”
Section: The Samplementioning
confidence: 68%
“…After distributing our questionnaire to these journals and sending out two reminders, we eventually obtained a total of 361 useful responses. The final response rate of 6.12% is low, but comparable to, or even higher than response rates of similar online surveys among journal editors or authors regarding issues related to academic integrity (Hopp and Hoover 2017;Stitzel et al 2018). Nevertheless, our sample covers a wide range of research fields and reflects the distribution of journals over fields.…”
Section: The Samplementioning
confidence: 68%
“…After the reminders, we eventually obtained a total of 361 useful responses. The final response rate of 6.12% is low, but comparable to, or even higher, than response rates of similar online surveys among journal editors or authors regarding issues related to academic integrity (Hopp and Hoover 2017 ; Stitzel et al 2018 ). Nevertheless, our sample covers a wide range of research fields and reflects the distribution of journals over research fields.…”
Section: Methodsmentioning
confidence: 67%
“…A later Internet survey by Enders and Hoover 40 indicated that approximately two-thirds of their sample believed that plagiarism could be addressed by a profession-wide code of ethics. Over 10 years later, Stitzel et al 41 expanded the Enders and Hoover 39 study to other disciplines and found that 45% of journal editors in their sample reported having instituted a formal plagiarism policy, against the 19% reported in the Enders and Hoover 39 study. Stitzel et al 41 believe that, increasingly, the problem of plagiarism is being taken more seriously, with approximately 80% of journal editors suggesting that when clear-cut plagiarism is detected, it would be appropriate to ban the plagiarist from submitting future work to the journal.…”
Section: Role Of Journal Editors and Publishers In Addressing Plagiarismmentioning
confidence: 99%